Effect of DcR3-specific siRNA on cell growth suppression and apoptosis induction in glioma cells via affecting ERK and AKT - Zhang, Yu (Onco Targets Ther, 2016)
BACKGROUND: Previously, we found that the expression of decoy receptor 3 (DcR3) in gliomas was significantly upregulated compared to normal brain tissues. However, the effect of DcR3-specific small interfering RNA (siRNA) on cell biological function of glioma cells remains incompletely understood. OBJECTIVE: The aim of this study was to explore the effect of DcR3 siRNA on cell growth and apoptosis of glioma cells and to investigate the potential downstream pathways affected by DcR3. METHODS: DcR3-specific siRNA was transfected into three glioma cell lines (U251MG, LN-308, and U87MG) using combiMAGnetofection method. MTS tetrazolium assay and fluorimetric resorufin viability assay were used to assess the growth of glioma cells. Then, apoptosis was examined using the Hoechst 33342/propidium iodide double-staining assay and fluorescent caspase-3/7 assay. Meanwhile, Western blot was performed to explore the probable pathway by which DcR3-specific siRNA acts in glioma cells. Also, microarray dataset analysis was applied to analyze the potential function of DcR3 in glioma. RESULTS: The DcR3-specific siRNA had a potent effect on cell growth and apoptosis of all three glioma cells tested, and the effects were time dependent. Among these three glioma cell lines, U251MG had the most significant effect with regard to growth inhibition and apoptosis induction. MTS assay showed that the proliferation rate at 72 and 96 hours after the transfection was 76.333%±5.131% (t=7.611, P=0.002) and 64.333%±5.859% (t=10.983, P<0.001), respectively. The viability rate of U251MG cells was 80.667%±2.309% (t=12.302, P<0.001) and 62.333%±2.082% (t=21.213, P<0.001) at 72 and 96 hours posttreatment, respectively. The caspase-3/7 activity of U251MG cells was 2.76 (t=−6.601, P=0.003) and 4.75 (t=−9.189, P=0.001) folds that of the mock control at 72 and 96 hours, respectively. The apoptosis rate was increased to 1.85 (t=−2.496, P=0.067) and 3.93 (t=−12.587, P<0.001) folds at 72 and 96 hours after transfection, respectively. Furthermore, the levels of phospho-ERK1/2 and phospho-AKT were significantly downregulated after DcR3 silencing. CONCLUSION: The DcR3-specific siRNA could efficiently inhibit growth and induce apoptosis of cells via affecting ERK and AKT. Hence, DcR3-specific siRNA treatment could act as a supplementary targeted therapy strategy for gliomas.